Critical Discourse Analysis of the Teun A. van Dijk Paradigm on the News Entitled "Viral! Husband in East Jakarta Was Assaulted and Dragged by a Car When He Caught His Wife Cheating" on Detik.com - Zidan Rizka Alhafidz (Communigate, 2025)
This research focuses on the critical discourse analysis of Teun A. van Dijk's paradigm as applied to the news article published on Detik.com titled "Viral! Husband in East Jakarta Was Assaulted and Dragged by a Car When He Caught His Wife Cheating." The study employs a qualitative descriptive method with techniques including observation and reading, data classification, analysis, presentation, and conclusion. The findings indicate that the news article aligns with the critical discourse analysis model, encompassing text structure (macrostructure, superstructure, microstructure), social cognition, and social context as outlined in Teun A. van Dijk's theory. This research contributes to discourse analysis scholarship by illustrating how van Dijk's theoretical framework can reveal the underlying structural and social dimensions of contemporary digital news media.